Total Phenolic, Flavonoid Content, and Antioxidant Activity of Ethanol Extracts and Flour from Pereskia sacharosa Griseb (Cactaceae) Leaves - Junaidi, Junaidi; Suroto, Dian Anggraini; Mayangsari, Yunika (Indonesian Food and Nutrition Progress, 2026)
Pereskia sacharosa is an unconventional food plant found in several regions, especially in Indonesia. Traditionally, the leaves of this plant are used as medicine for pain, allergies, and fever. This study aims to identify several bioactive compounds from the ethanol extract and flour of Pereskia sacharosa through the maceration method using 80% and 96% ethanol. In addition, phytochemical and antioxidant activity tests were carried out. The total phenolic content in the 80% ethanol extract, 96% ethanol extract, and Pereskia sacharosa leaf flour was (34.83 ± 0.89 mg GAE/g, 30.04 ± 0.67 mg GAE/g, and 5.66 ± 0.23 mg GAE/g), respectively. The total flavonoid content in the 80% ethanol extract, 96% ethanol extract, and Pereskia sacharosa leaf flour was (17.05 ± 1.70 mg QE/g, 15.40 ± 0.93 mg QE/g, and 8.01 ± 0.58 mg QE/g), respectively. Statistical analysis showed a significant difference (P < 0.05) between the extract samples and the leaf flour sample. The antioxidant activity, measured by IC50 values, was moderate for the 80% ethanol extract (251.09 ± 0.02 ppm) and 96% ethanol extract (204.55 ± 0.10 ppm) of Pereskia sacharosa leaves. In contrast, the leaf flour exhibited weak antioxidant activity, with an IC50 value of 571.88 ± 0.18 ppm.